PENEGAKAN HUKUM TERHADAP GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU - H, Astrina; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The existence of homeless and beggars who are increasingly 'rampant' in the city of Pekanbaru, clearlydisturbing the comfort of the community, especially road users, because these homeless and beggars often roamthe intersections and streets of the city center by acting improperly. Homelessness and begging activities arequalified as a criminal offense, namely as a violation (overtredingen) in the field of public order. Bums andbeggars who disturb public order in Pekanbaru City are only given sanctions in the form of fostering and afterfostering the homeless and beggars are returned to their respective areas of origin. With a high number ofhomeless people, it cannot be denied that crimes or other criminal acts such as theft, robbery or murder willarise. Law enforcement in such disclosures can be expected to be effective because it is a violation of the lawthat can be life-threatening. Therefore the purpose of this thesis, namely: first, how is law enforcement againstbeggars and homeless people in the city of Pekanbaru? Second, what are the obstacles in law enforcementagainst beggars and homeless people in the city of Pekanbaru?This type of research used in this study is empirical juridical or sociological legal research. Empiricaljuridical research is carried out by carrying out legal identification and how the effectiveness of that lawapplies in society. Sources of data used, namely: primary data and secondary data. Data collection techniques,namely interviews and literature review, as well as this study were analyzed using qualitative analysis.The conclusion that can be obtained from the results of the first research, law enforcement of Article504 and Article 505 of the Criminal Code and Article 3 jo Article 29 (paragraph 1) of Regional RegulationNumber 12 of 2008 concerning Social Order is not yet optimal. This is proven by the fact that not all of thecriminal sanctions provided for in these provisions are carried out by the Satpol PP and Pekanbaru City Socialand Funeral Services. Second, barriers to the realization of law enforcement against homeless and beggars inthe city of Pekanbaru, are caused by lack of awareness of the community as homeless and beggars, limitedfacilities and infrastructure, weak supervision from the government and are not subject to sanctions forhomeless and beggars. Suggestions for the future are expected that the Pekanbaru City Social and FuneralService of the Civil Service Police Unit maximizes its role by continuing to pay attention and improve thequality of performance to resolve issues of social welfare that occur in the community, in addition it needs to bethoroughly evaluated and improved that must be immediately carried out by the Pekanbaru City Governmentand related law enforcement officials overcoming obstacles in law enforcement against the homeless andbeggars.Keywords: Enforcement-Homelessness and Beggars-Pekanbaru